Politics of COVID-19 vaccination in Japan: how governing incumbents' representation affected regional rollout variation - M. Kikuchi; S. Ishihara; M. Kohno (BMC, 2023)
Abstract Background Despite initial delay, Japan's COVID-19 vaccination accelerated remarkably from May to September 2021 under the leadership of Prime Minister Yoshihide Suga. His "campaign" for vaccination, however, did not yield uniform results nationwide. Methods To highlight political determinants for the regional variation, we employ ordinary least squares regression analyses to investigate how the share/presence of incumbent politicians belonging to the governing parties, the Liberal Democratic Party and Komei Party, influenced the varying progress of rollouts across prefectures as well as across cities/towns/villages. The data on the vaccination rate for all 47 prefectures was obtained from Government Chief Information Officer (CIO)'s Portal, Japan (GCPJ) approximately one month prior to the anticipated general election, the national election for the more important House of Representatives of Japan's bicameral parliament (Diet). The data for lower administrative units, though its availability was limited to only three prefectures, was obtained from the respective governments of Kagawa and Ehime and from a local newspaper in Gifu. Results The findings reveal that at both prefectural and sub-prefectural administrative levels, the share/presence of the governing parties' representation in the national parliament had a positive and statistically significant effect on the region's vaccination progress, after controlling for the local proliferation of COVID-19 and demographic characteristics. Conclusion Our findings contribute insights into the understudied area of the contemporary COVID-19 health environment, namely how the political dynamics of democracy affect the pattern of vaccine dissemination in Japan. Trial registration : Not applicable.